Synergistic Effect of Capparis Spinosa Fruits Extract in Comparison with Ciprofloxacin Against Resistant E. Coli O157:H7 - Ali H. Saliem; Reham Najem Abdulridha (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted to evaluate the synergistic effect between Capparis Spinosa fruits methanolic extract and ciprofloxacin against resistant E. Coli O157:H7, in varying concentration. This experiment was carried out through the ultrasonic alcoholic extraction of C. Spinosa fruits, and an extraction ratio of 24% was obtained. The extract showed pronounced concentration dependent antibacterial activity. The susceptibility study revealed that E. Coli O157:H7 was sensitive to C. Spinosa fruits. The findings of the present study indicate that the use of pronounced C. Spinosa fruits extract may have the perfect to be choice in clinical control. The concentration of C. spinosa fruits extract increase the activity of inhibition, increase as well when used in combination with ciprofloxacin (half concentration from each other). In result appeared synergism effect between plant extract and ciprofloxacin and may make bacteria lost their resistance to antibiotics by this synergism phenomenon. The result of MIC (6400 µg/ ml), MBC (12800 µg/ ml) and for C. spinose fruits extract while ciprofloxacin MIC (12.5 µg/ ml) and MBC (25 µg/ ml). MICs of CIP/ C. spinosa fruits extract combinations against E. coli O157:H7 isolate was 1.562/ 1600 μg/ml. Value of minimum bactericidal concentration (MBC) of the synergistic combinations (CIP/ C. spinosa fruits extract) was 3.124/ 3200 μg/ml. According to obtained results fractional inhibitory concentration (FIC) value of (CIP/ C. spinosa fruits extract 1.562/ 1600 μg/ml) was (0.375) less than 0.5 indicates synergistic effect of interaction.